Pembelajaran Organisasi di Pondok Pesantren - Nurhadi, Nurhadi (Taallum: Jurnal Pendidikan Islam, 2013)
Pesantren as social religious organization plays important role in implementing the concept of education for all. Such concept accommodates the belief that every human being holds a right to be educated either formally or informally. The implication is throughÂ  pesantren, somebody may learn to live a life well. Further, pesantren is responsible to develop its students to become intelligent and pious.